Impact evaluation of skin color, gender, and hair on the performance of eigenface, ICA, and, CNN methods - Mirzaei, Muhammad Ehsan (2020)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence